ANALISIS MANAJEMEN SUMBER DAYA MANUSIA DALAM PEMBANGUNAN ANGKATAN KERJA DI DESA SUKAMAJU - Violla Fransisca; Indra Aditya; Dewi Noor Azijah (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
The unemployment rate in Sukamaju Village remains very high, primarily due to the low level of education among its residents. This study aims to identify and analyze the efforts undertaken by the Sukamaju Village government to improve human resources and their implications for the local labor force. The study uses data collected through interviews, observations, and documentation. Gary S. Becker’s Human Capital Theory, which consists of three indicators (1) education, (2) skills and training, and (3) work experience is applied to support the data analysis.The findings show that: (1) the educational level of the Sukamaju Village community is still relatively low, with most residents having only primary and secondary school education; (2) the training programs implemented in Sukamaju Village have not yet been optimal; and (3) the majority of residents have work experience in the informal sector, such as laborers, construction workers, and small traders.Theoretically, this study contributes to the development of insights and literature on human resource and labor force management. Practically, it provides input for the government and Sukamaju Village to continue strengthening efforts to improve the quality of human resources.